HE EXPERIENCE OF SI: THE INTERTRACTIONS AND INTERFACES OF THE DISSEMINATION OF KNOWLEDGE IN TEACHING TRAINING - Alves de Souza, Amilton; Eurico Rodrigues Matta, Alfredo; Amorim, Antonio (LINKSCIENCEPLACE, 2026)
In this article we propose to analyze how the experiences of themselves contribute in the continued teacher formation. We propose as specific objectives: to identify the teacher perceptions about the experiences of self and the subjectivity; To perceive which models of experiences are constructed in the classroom, having ICT as an interface; Reflect epistemologically on the experiences, subjectivity, diffusion of knowledge and teacher training, from the experiences of the school. The problem investigated had the following question: How to think about continuing teacher formation, based on the experience of self? This research used the qualitative approach with an online questionnaire instrument, which includes issues of teacher education, subjectivity and ICT with focus, in order to establish a relationship between teacher training and experience. The research opens new possibilities about continuing teacher education and re-signification other senses of learning and knowledge from the teaching practice, appropriating themselves through their experience through dialogic principles, critical reflexivity and encounter with the other.